Avaliação da satisfação dos usuários do Sistema Único de Saúde com os serviços de saúde no município de Pato Branco - PR - Souza, Luane Paula de (2020)
SUS develops its regulation policy through organizational principles that describe the quality of the service provided based on popular participation.Health services have a complex servicespace in which customers analyze quality customers analyze the quality of the service in view of both the result and the experience. In this context, the aim of this study is toassess SUS user satisfaction with health services using an instrument developed from the context of public health, with the study an evaluation survey of SUS health services in the Pato Branco county state of Paraná. For this, the literature sought relevant aspects for assessing the health quality of construction, a questionnaire was formulated to assess user satisfaction in the SUS with health services and it was validated through the Lawshe Method. The weights of each construct were defined by the AHP multicriteria decision support method, as well as the weights of each item in the questionnaire. The adapted scale of the satisfaction continuum was used to anchor the responses of the data collection with 99 SUS users in the Pato Branco county state of Paraná. The results suggest 7 quality assessment constructs in which all questions in the questionnaire were important to compose the validated questionnaire. The construct that contributes the most to the total weight of the constructs refers to C3-Courtesy,dignity and respect. Within the scale of satisfaction with health services, the surveyed sample is satisfied with most of the analyzed constructs, except for the C1-Infrastructure constructs and C7-Health service recommendation, in which the sample is dissatisfied.